Okun's law in Austria - Michael Christl; Monika Köppl-Turyna; Dénes Kucsera (DANUBE: Law, Economics and Social Issues Review, 2017)
We estimate the classic and the dynamic variant of Okun's law for the Austrian labor market. We find that, for recent periods, the growth rate necessary to stabilize the unemployment rate equals 2.8 percent. Moreover, we find that the rate has been growing in recent quarters due to the increasing labor force size and the effects of the crisis. The latest prediction of the employment threshold lies above 3 percent, much above forecasted GDP growth up to 2017.
Keywords: 330; Unemployment; Growth; Okun's Law; Austria